A Phonetic, Morphological and Semantic Analysis of Arabic Words in Malay - Abukhudairi, Arif Karkhi (Journal of Modern Languages, 2017)
This study considers ‘loanwords’, as a universal phenomenon, as there is no language which does not borrow lexical items from other languages either to adopt new concepts or to enrich, increase and develop its vocabulary. Arabic loanwords in Malay have been subjugated to various kinds of change in conformity with the phonetic and morphological system of the Malay language. Exposed to so many Malay features, Arabic words have been greatly removed from their origin. Moreover, the Malay's adoption of the Latin script in the 1960's helped to further change the spelling of the words. This development has contributed to the phonetic corruption of the words and the distortion of their pronunciation.